Risk Allocation in Public Private Partnership (PPP) Project: A Review on Risk Factors - Abd Karim, Nur Alkaf (International Journal of Sustainable Construction Engineering and Technology, 2011)
It is important for the public and private sectors to establish effective risk allocation strategies for Public-Private Partnership (PPP) projects. According to Malaysia’s PPP Guideline, one of the key feature or characteristics is to optimal sharing of risk whereby risk is allocated to the party who is the best able to manage. This mean that in PPP itself, it emphasis risk allocation in construction project. This paper presents on reviewing the risk factors of PPP construction project by mapping previous research works on PPP project around the world. The matrix of the mapping gives the frequency of factors that are considered the risk allocation of PPP project. The risk factors are clustered into 10 groups namely: Political, Construction, Legal, Economic, Operation, Market, Project selection, Project finance, Relationship and Natural factor. Result shows that the highest score frequency factors are change in law, delay in project approvals & permits and land acquisition. By knowing the risk factors gives better understanding in allocating them to parties/stakeholders involved.